Effects of hemodialysis with cooled dialysate on high‐sensitivity cardiac troponin I and brain natriuretic peptide. Issue 4 (18th July 2022) - Bathish, Younes; Beiruti, Karine; Safadi, Hussein; Nov, Adi Sharabi; Bukovetzky, Elena; Edelstein, Michael; Halabi, Majdi; Israeli, Zeev
Abstract: Background: Hemodialysis (HD) triggers recurrent and cumulative ischemic insults to the brain and the heart. Cooled dialysate may have a protective effect on major organs and improve hemodynamic tolerability of dialysis. The aim of the study was to compare HD with cooled dialysate with routine dialysis in terms of hemodynamic stability and levels of high‐sensitivity Troponin I (hs‐TnI) and N‐terminal pro b‐type natriuretic peptide (NTproBNP) pre and postdialysis. Methods: The 45 patients were randomized into two groups. The first group received a 35.5°C dialysate first (hypothermic dialysis) and the second group a 36.5°C dialysate first (routine dialysis). Then groups crossed over, so each group received the alternate dialysate (self‐controls) For each patient, the first sample was collected at the beginning of dialysis, and a second sample was taken at the end of dialysis. Results and conclusion: hs‐TnI and NTproBNP increased after routine HD by 10.7 ng( p < 0.001) and (12.0 pg/μl) ( p < 0.001), respectively, and by −3.1 ng( p = 0.25) and (4.3 pg/μl) ( p < 0.001), respectively after hypothermic HD. Our study results showed a tendency towards less rise in hsTnI and NTproBNP during hypothermic HD (35.5°C) as compared to routine HD (36.5°C). Neither arm experienced statistically significant changes in blood pressure. Further studies in larger cohorts and long follow up are warranted in order to confirm that lower rise in (hs‐TnI) and NTproBNP actually translate into lower clinical risk for cardiovascular events.